Roles in Cell-to-Cell Fusion of Two Conserved Hydrophobic Regions in the Murine Coronavirus Spike Protein() - Luo, Zongli (Virology, 1998)
The spike (S) protein of coronavirus, mouse hepatitis virus (MHV), mediates attachment and fusion during viral entry and cell-to-cell fusion later in infection. By analogy with other viral proteins that induce cell fusion the MHV S protein would be expected to have a hydrophobic stretch of amino acids that serves as a fusion peptide. Sequence analysis suggests that the S protein falls within the group of fusion proteins having internal rather than N-terminal fusion peptides. Based on the features of known viral fusion peptides, we identified two regions (PEP1 and PEP2) of MHV-A59 S2 as possible fusion peptides. Site-directed mutagenesis and anin vitrocell-to-cell fusion assay were used to evaluate the roles of PEP1 and PEP2, as well as a third previously identified putative fusion domain (PEP3) in membrane fusion. Substitution of bulky hydrophobic residues with charged residues within PEP1 affects the fusion activity of the S protein without affecting processing and surface expression. Similar substitutions within PEP2 result in a fusion-negative phenotype; however, these mutant S proteins also exhibit defects in protein processing and surface expression which likely explain the loss of the ability to induce fusion. Thus PEP1 remains a candidate fusion peptide, while PEP2 may play a significant role in the overall structure or oligomerization of the S protein. PEP3 is an unlikely putative fusion peptide since it is not conserved among coronaviruses and nonconservative amino acid substitutions in PEP3 have minimal effects on cell-to-cell fusion.